Study of fungal degradation products of polycyclic aromatic hydrocarbons using gas chromatography with ion trap mass spectrometry detection - Cajthaml, Tomás; Möder, Monika; Kacer, Petr; Sasek, Václav; Popp, Peter (Journal of chromatography. A, 2002)
Representatives of polycyclic aromatic hydrocarbons (PAHs) were degraded by ligninolytic fungus Irpex lacteus. The products were analyzed by GC-Ion trap mass spectrometry. The combination of full scan mass spectra, product ion scans (MS-MS) and derivatization of the degradation products of anthracene, phenanthrene, fluoranthene and pyrene provided further insight in the degradation mechanism initiated by I. lacteus. Particularly, the product ion scans enabled the interpretation of unknown degradation products, even though they were only produced at trace level. Most of the structures suggested were later confirmed with authentic standards.
Keywords: houby; polycyklické sloučeniny; Polycyclic Compounds; Fungi; Gas Chromatography-Mass Spectrometry; plynová chromatografie s hmotnostně spektrometrickou detekcí